1948
DOI: 10.1172/jci102016
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Methionine and Sulfur Metabolism. I. The Fate of Intravenously Administered Methionine, in Normal Individuals and in Patients With Liver Damage 12

Abstract: The cardinal role of the liver in protein and amino acid metabolism has been well established. Consequently, studies of amino acid metabolism occupy a natural and fundamental place in an investigation of metabolic aberrations in hepatic disease. In 1913, Van advantage since this serves as a "label" in the interpretation of the metabolic fate of the administered methionine.In the present study a standard dose of DLmethionine was administered intravenously. Observations were then made on the rate of disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1949
1949
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 6 publications
1
21
0
2
Order By: Relevance
“…The data for leucine reported by the latter investigators were obtained by the oxidative method of Fromegat which, according to Hier et al (22) (23). The present data for free amino acids in plasma agree with the findings of Hier and Bergeim (24) in a group of 33 normal persons, and with the results for valine and histidine reported by Ackermann et al (25).…”
Section: Comment Plasmasupporting
confidence: 90%
“…The data for leucine reported by the latter investigators were obtained by the oxidative method of Fromegat which, according to Hier et al (22) (23). The present data for free amino acids in plasma agree with the findings of Hier and Bergeim (24) in a group of 33 normal persons, and with the results for valine and histidine reported by Ackermann et al (25).…”
Section: Comment Plasmasupporting
confidence: 90%
“…In 1948, Kinsell et al 20 demonstrated marked impairment in methionine clearance after a methionine load in patients with liver injury, thereby establishing the central role of the liver in methionine metabolism. Patients with liver cirrhosis have decreased SAMe biosynthesis because of decreased expression of MAT1A and lower hepatic MAT activity, 21,22 and treatment with SAMe increased hepatic GSH levels and increased survival in patients with less advanced alcoholic liver cirrhosis.…”
Section: Role Of Same In Liver Injurymentioning
confidence: 99%
“…That intravenously administered amino acids are rapidly removed by the tissues from the blood stream of the dog was shown many years ago by Van Slyke and Meyer (1,37). In man, also, intravenously administered glycine, methionine and lysine have been found to disappear rapidly (38)(39)(40). When the diet is the source of the additional amino acids, the liver assumes particular importance in their disposal.…”
Section: Dietary Ingredients Other Than Protein Maymentioning
confidence: 99%